KIA (KITÃ‚BAH ITU ASYIK): PENGEMBANGAN MULTIMEDIA BERBASIS ADOBE FLASH PROFESSIONAL CS6 PADA KETERAMPILAN MENULIS UNTUK SISWA KELAS X MA (Lisanul Arab: Journal of Arabic Learning and Teaching, 2018)
The problems on Arabic learning writing skills are difficult and tedious learning because of the absence oflearning media. For that, we need to develop a learning media that can improve motivation of students. Theform of learning media is a multimedia. Furthermore, that multimedia is called KIA (KitÃ¢bah Itu Asyik orwriting is fun). This multimedia is created by Adobe Flash Professional CS6 that is Adobe Systems' flagshipproduct. That purposes are: describe the requirements of teachers and students, KIAâ€™s media design, andexperts validity of KIAâ€™s products for Arabic writing skills for students of class X senior high school. The designis research and development (R&D) with steps: formulate the potential and problem, collect the informationand data, product design, product validity, and improve the product design. The conclusion of this study isteachers and students requires KIAâ€™s media based on their requirements analysis. KIAâ€™s media is made withadapted to the Arabic Curriculum on 2013 in the class X a year. The theme is consists of the initial appearanceof KIAâ€™s media, title, apperception, KI/KD, material, evaluation, profile, direction, and exit. The results ofproduct validity is stated that "reasonable" to be used. AbstrakPermasalahan pada pembelajaran keterampilan menulis Bahasa Arab yaitu pembelajaran yangsulit dan membosankan karena tidak adanya media pembelajaran. Untuk itu perlu dikembangkanmedia pembelajaran berupa multimedia. Selanjutnya multimedia tersebut dinamakan KIA(KitÃ¢bah Itu Asyik). Multimedia ini dibuat dengan menggunakan Adobe Flash Professional CS6yang merupakan produk unggulan Adobe Systems. Tujuan penelitian ini adalah mendeskripsikananalisis kebutuhan guru dan siswa, desain media, dan validitas ahli terhadap produk KIA(KitÃ¢bah Itu Asyik) untuk keterampilan menulis Bahasa Arab siswa kelas X MA. Desain penelitianini adalah research and development (R&D) dengan langkah: merumuskan potensi dan masalah,mengumpulkan informasi dan data, mendesain produk, validitas produk, dan revisi desain.Kesimpulan penelitian ini adalah hasil analisis kebutuhan menunjukkan guru dan siswamembutuhkan adanya media KIA. Media KIA tersebut dibuat sesuai dengan Kurikulum 2013Bahasa Arab pada kelas X selama satu tahun. Setiap tema terdiri dari tampilan awal, judul,apersepsi, KI/KD, materi, evaluasi, profil, petunjuk, dan keluar. Hasil validitas produkmenyatakan bahwa media KIA â€œlayakâ€ digunakan.